Social development through benevolent business / Kalyan Sankar Mandal - Mandal, Kalyan Sankar
This book points out that apart from usual "profit maximizing business," there exists other types of business models whose primary goal is to serve social causes and not just profit maximization. However, as we are schooled under the self-interest serving nature of human beings under capitalism, we are generally oblivious about the not-so-common existence of business models aimed at serving social goals. The book discusses with examples, business models that aim at serving social goals in a self-sustaining manner. Thus, the business models discussed in this book are social business, compassionate business, microfinance-based business, cooperative business, business aiming at "Bottom of the Pyramid," and social welfare business. The common point of all these business models is that they promote benevolence to society through business, which is not necessarily true for an usual profit maximization business. All these business models alleviate poverty and promote social development in a self-sustaining manner. The book identifies the main principles followed by these business models and based on the principles identified, it suggests a unique business model which we call as "benevolent business model." Thus, through this book, the students not only become aware and acquainted with the winning principles of social purposes-serving business models, most importantly, they will also get an idea about how to design a successful benevolent business. The author argues that along with the government and the NGOs, which are presently expected to meet social developmental needs, benevolent businesses should be promoted for meeting social developmental needs of the people, particularly of the poor.